Eccrine Duct Dilation as a Marker of Cicatricial Alopecia. (September 2017) - Tan, Timothy; Guitart, Joan; Gerami, Pedram; Yazdan, Pedram
Abstract : Background: Eccrine duct dilation (EDD) and syringoma-like sweat duct proliferation have been described as reactive changes occurring in a variety of skin conditions. However, extensive evaluation of EDD in scalp biopsies performed for alopecia has not been performed. Methods: We retrospectively examined 129 cases of cicatricial alopecia (lichen planopilaris, central centrifugal cicatricial alopecia, and discoid lupus erythematosus) and 130 cases of noncicatricial alopecias (androgenetic alopecia, telogen effluvium, and alopecia areata) for the presence of EDD. Results: Overall, EDD occurred in 4% (5/130) of noncicatricial alopecia (2/43 of androgenetic alopecia, 0/15 of telogen effluvium, 3/72 of alopecia areata) and 35% (45/129) of cicatricial alopecia (10/31 of lichen planopilaris, 17/36 central centrifugal cicatricial alopecia, and 18/62 of discoid lupus erythematosus; P < 0.0001) cases. Conclusions: EDD can infrequently occur in noncicatricial alopecias; however, the frequency of dilation is significantly increased in cicatricial alopecias. This alteration may be due to compressive or inflammatory effects inherent to the scarring process. The presence of EDD may be a useful adjunctive histopathologic feature in the diagnosis of cicatricial alopecias.